Reduction of Antibiotics Used in Newborn Babies Admitted to Neonatal Unit: A Quality Improvement Initiative - Narendra Behera; Jayanti Prava Behera; Siba Sankar Beriha; Abinashi Sabyasachi Sethy; D Joe Bennet; Deepnwita Patra; Arun Kumar Patra; Ranjan Kumar Barik (JCDR Research and Publications Pvt. Ltd., 2019)
Introduction: Excess exposure of antibiotics early in life disrupts the developing microbiome in skin and gastrointestinal system of new born which may lead to development of different health conditions. Prolong use of antibiotics in Neonatal Intensive Care Unit (NICU) develops resistance to infection, increases risk of Necrotizing Enterocolitis (NEC) and invasive fungal infection in new born. Studies reported that short course of antibiotics prevent treatment failure, cause reduction of duration of hospital stay, prevent antimicrobial resistance, decrease neonatal mortality and improve neurological outcome. Aim: This Quality Improvement (QI) study aimed to establish a standard guideline for reduction of antibiotics use in new born unit of a tertiary level health care institution of India. Materials and Methods: This QI study was conducted in the newborn units of paediatrics department of a tertiary health care center, Odisha, India, from 1st June to 31st July, 2018. Patients, under antibiotic therapy, were enrolled in this study. The data were collected in a predesigned case record form regarding duration, indications (as per the minimal investigation for sepsis, as per minimal risk factor for antibiotics used, as per high index of suspicion) and outcome in terms of cured, death and LAMA (Leave Against Medical Advice). Baseline data regarding the use of antibiotics were collected for one month period and final data for another one month were collected after applying newly formed antibiotic use guideline among neonates. Data were analysed by Chisquare test using Graph pad prism ver. 0.5. Results: In this study distribution of antibiotic used among hospitalised patients in post-intervention phase was significantly decreased (77%) compared to baseline data (94%). This study result showed that percentage of cases using antibiotics, were not as per risk factors and were reduced significantly, post implementation of guidelines. Antibiotic used, as per the high index of suspicion increased (76%) significantly compared with baseline data (27%) and also as per the systemic sign of sepsis increased significantly in final data (74.04%) over baseline data (48%). Antibiotic use duration was reduced in post-intervention period i.e., ≥3 days over ≥5 days (baseline data) significantly. There was no significant difference in outcomes. Conclusion: On application of newly formed antibiotic use guideline with reduced antibiotic use strategy, the final data compared with baseline data did not show any significant difference in cure rate as well as death/LAMA/referred.